PROPOSED DIGITAL MEDIA OUTREACH STRATEGY FOR ENVIRONMENTAL MEDIA IN INDONESIA: A STUDY ON ENVIRONEWS INDONESIA - Arum Verselita, Akita
Environews Indonesia is an environmental-focused digital media, established in 2012 as a part of Environews Worldwide and Environews.org based in California in the United States. Environews Indonesia presents a website that publishes substantial environmental subjects in Indonesia. It operates using the funding or organization or individual donor. The donors provide Environews Indonesia monetary and non-monetary supports for Environews Indonesia to run, in exchange for creating impacts in regulation, to be a reliable reference source platform and rise of environmental awareness in society. As Environews Indonesia responsible to the donors, Environews Indonesia has to grow their presence in the digital media industry in Indonesia and to be able to position itself as the prominent environmental media in Indonesia, and in order to be able to gain the credibility as well as to expand their readership and awareness through a media outreach program. Thus, this study examines the current condition of the program conducted using internal and external approaches such as Business Model Canvas, STP Analysis, and PESTEL Analysis. The retrieved data then used to develop media outreach strategy based on the tools of digital media framework such as The Five C’s Framework and Active Media Framework. The proposed solutions presented using the tools of SWOT Analysis and TOWS Matrix. The result of the strategy formulation is expected to be able to be implemented as a practical strategy for the media outreach expansion of Environews Indonesia that is impactful for the business process in the short run and sustainable for the long term. And for the conclusion, Environews Indonesia has the favor in their side to be established and continuously nurtured as the environmental news platform with quality content. At the same time, they have to maintain the current strength and retain its current capitals. They shall provide the diversification of content for their segments that requires creativity and consistency to do so. Collaboration is also the key. The presentation of the message supposed to be varied to accommodate the trend. Thus, regular research shall be regularly conducted. Lastly, the offline and online outreach has to be also maintained.